Monolayer MoS2 with S vacancies from interlayer spacing expanded counterparts for highly efficient electrochemical hydrogen production. Issue 42 (7th October 2016) - Xu, Yuzi; Wang, Longlu; Liu, Xia; Zhang, Shuqu; Liu, Chengbin; Yan, Dafeng; Zeng, Yunxiong; Pei, Yong; Liu, Yutang; Luo, Shenglian
Abstract : Monolayer MoS2 nanosheets with activated basal planes have been prepared using a simple hydrothermal method. Abstract : It is challenging to prepare monolayer MoS2 with activated basal planes in a simple and efficient way. In this study, an interlayer spacing expanded counterpart, ammonia-intercalated MoS2, was obtained by a simple hydrothermal reaction of ammonium molybdate and elemental sulfur in hydrazine monohydrate solution. Then, the ammonia-intercalated MoS2 could be easily exfoliated by ultrasonication to get monolayer MoS2 . Importantly, this monolayer MoS2 possessed rich S vacancies. The produced MoS2 demonstrated a proliferated active site density as well as low-loss electrical transport for efficient electrochemical hydrogen production from water. As expected, the monolayer MoS2 with S vacancies exhibited an excellent electrocatalytic hydrogen evolution reaction performance with a low overpotential (at 10 mA cm −2 ) of 160 mV (V vs. RHE) in acid media and a small Tafel slope of 54.9 mV dec −1 . Furthermore, the catalyst displayed a good long-term stability and chemical stability during the electrochemical hydrogen production process. Computational studies prove that the S vacancies enabled the inert basal planes by introducing localized donor states into the bandgap and lowered the hydrogen adsorption free energy. This study could open new opportunities for the rational design and a better understanding of structure–property relationships of MoS2 -based catalysts for water splitting or other applications.